Association of sleep duration and physical frailty with cognitive function in older patients with coexisting atrial fibrillation and heart failure - Eun Ji Seo; Mi Hwa Won; Youn‐Jung Son (Wiley, 2023)
Abstract Aim To investigate the associations of sleep duration and physical frailty with cognitive function in older patients with both atrial fibrillation and heart failure. Design This study used a cross‐sectional, secondary data analysis design. Method We included outpatients aged ≥ 65 years with coexisting atrial fibrillation and heart failure in South Korea. We used a sample of 176 patients (men = 100) with HF among 277 data from the parent study. The data were collected through a self‐report, structured questionnaire and electronic medical record. Results Our main finding showed that long sleep duration and physically frail status were significant predictors of cognitive impairment in older adults with both atrial fibrillation and heart failure. Healthcare providers should be aware of the importance of assessing sleep duration and physical activity in older adults with both atrial fibrillation and heart failure to prevent or delay cognitive impairment.